2012
DOI: 10.1002/aenm.201200532
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Semi‐transparent Polymer Solar Cells with Transparency Color Rendering Indices approaching 100

Abstract: Window‐ or building‐integrated semi‐transparent solar cells are particularly interesting applications for organic photovoltaic devices. In this work, we present an easy‐to‐process inverted device architecture comprising fully solution processable poly(3,4‐ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) bilayer top‐electrodes for efficient semi‐transparent organic solar cells. By incorporating dyes with a complementary absorption to the light harvesting polymer poly[[9‐(1‐octylnonyl)‐9H‐carbazole‐2,7‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 17 publications
2
56
0
Order By: Relevance
“…There are several organic-based approaches that produce semi-transparent OPV devices that exhibit good electrical performance (Figure 8), whereby they are composed of organic electronic materials, and transparent electrodes based on a wide range of different materials, including conducting polymers [122][123][124][125], thin metal films [126], sputtered transparent conducting oxides of LiCoO2/Al [127], carbon nanotubes [122], graphene [128], and silver nanowires (Ag NWs) [129][130][131][132][133]. Recently, a study by Beiley et al [134], has shown the development of a semi-transparent OPV which consists of a silver nanowire (Ag NW) and zinc oxide nanoparticle (ZnO NP) composite top electrode, and has a power conversion efficiency of 5.0%.…”
Section: Organic Photovoltaics (Opvs)mentioning
confidence: 99%
“…There are several organic-based approaches that produce semi-transparent OPV devices that exhibit good electrical performance (Figure 8), whereby they are composed of organic electronic materials, and transparent electrodes based on a wide range of different materials, including conducting polymers [122][123][124][125], thin metal films [126], sputtered transparent conducting oxides of LiCoO2/Al [127], carbon nanotubes [122], graphene [128], and silver nanowires (Ag NWs) [129][130][131][132][133]. Recently, a study by Beiley et al [134], has shown the development of a semi-transparent OPV which consists of a silver nanowire (Ag NW) and zinc oxide nanoparticle (ZnO NP) composite top electrode, and has a power conversion efficiency of 5.0%.…”
Section: Organic Photovoltaics (Opvs)mentioning
confidence: 99%
“…[20][21] Along with the investigation, the STPSC with high efficiency and transmittance cannot meet BIPV application requirement, such as the building aesthetics and natural transmitted light. 29 However, the obtained higher CRI was always accompanied with lower PCE. It means that the light transmitted though STPSCs window can keep the neutral color property of the incident light source, such as a sun or a lamp.…”
Section: Introductionmentioning
confidence: 92%
“…[12][13][14][15][16] BIPV is a novel application of solar energy, which has been considered as an attractive research based on the combination of large area building and huge photovoltaic market. [27][28][29][30] The neutral color degree of transmitted light is dependent on the value of CRI by calculating. [20][21] Along with the investigation, the STPSC with high efficiency and transmittance cannot meet BIPV application requirement, such as the building aesthetics and natural transmitted light.…”
Section: Introductionmentioning
confidence: 99%
“…16 Then, the color rendering index (CRI) of STPSC, which is a quantitative parameter of neutral color property, began to mentioned. [17][18][19][20] It is well known that the CRI is a quantitative measure of the ability of a light source to reveal the colors of various objects faithfully in comparison with an ideal light source, which is defined by the Commission Internationale de L'Eclairage (CIE, in French). [21][22][23] Light sources with a high CRI are desirable in color-critical applications such as neonatal care, photography and cinematography.…”
Section: Introductionmentioning
confidence: 99%